Causal relationship between school-entry age and adolescent health: quasi-experimental evidence from 1.6 million participants in Vietnam - Busireddy, Ishaan; Liao, Janny; Nguyen, Hoa Thi; Dat, Vu; Minh, Tam Tran Ngo; Thuc, Duc Le; De Neve, Jan-Walter (medRxiv, 2024)
Background School-entry age has been suggested to affect human capital development. Little is known, however, about the impacts of school-entry age on adolescent health in low- and middle-income countries where most children and adolescents worldwide reside. - Methods Data on children’s outcomes were extracted from the longitudinal Young Lives Study in Vietnam, conducted between 2001 and 2016 (N=1,532), and the Vietnam Population and Housing Censuses of 1989, 1999, and 2009 (N=1,595,365). In Vietnam, children need to turn six years old by December 31st to enter Grade 1 in September that school year. As a result of the school-entry age policy, children born on or before December 31st start school one year earlier compared to children who are born just after December 31st. Using exposure to the policy as an exogenous instrument for school-entry age, we used two-stage least squares regressions to determine the causal effect of school-entry age on education and health outcomes by age 23 years. We considered pre-primary education, school attendance, time spent in school, childbearing, marriage or cohabitation, as well as anthropometric measurements. - Results Children born after the school-entry age cut-off were more likely to have participated in pre-primary education and were more likely to be in school when compared to children born before the cut-off. A one-year increase in age at the beginning of Grade 1 because of the policy was associated with an increase in the probability of pre-primary education of 13 percentage points (95% CI: 7.8-18.5), daily time spent in school of 0.9 hours (95% CI: 0.5-1.4) and a reduced probability of having an own child of 25.3 percentage points (95% CI: 4.4-46.2). We observed a qualitatively smaller and statistically non-significant relationship between school-entry age and measured body mass index. These results were generally consistent when using alternative specifications of our model, sample, survey rounds, and data sources. - Discussion Children who are older when entering primary school stayed in school longer and postponed family formation compared to children who entered school earlier because of the school-entry age policy in Vietnam. Relative age for grade should be considered when designing sexual and reproductive health interventions and programs targeted to adolescents.
Gesehen am 23.02.2026